Состав шихты для получения кордиеритовой керамики - Хабас Т. А. Тамара Андреевна; Костяная Е. А.; Верещагин В. И. Владимир Иванович; Ильин А. П. Александр Петрович; Кирчанов А. А.; Вакалова Т. В. Татьяна Викторовна
опубл. 27.08.03, Бюл. № 24